Toscana bilingue (1260 ca.-1430 ca.) Per una storia sociale del tradurre medievale - Montefusco, Antonio; Bischetti, Sara; Lodone, Michele; Lorenzi, Cristiano (Toscana Bilingue. Storia sociale della traduzione medievale / Bilingualism in Medieval Tuscany, 2021)
The contributions gathered in this volume discuss the complex topic of translating in medieval itay from an interdisciplinary perspective, combining the philological approach with a detailed social and cultural analysis. The authors discuss, among other topics, translations of 'classical' and particularly so-called 'modern' texts, the distribution of knowledge and languages, and the social history of translating.